Cummins Generator Technologies India Limited : building India's first green factory - Varkkey, Biju, (SAGE Knowledge. Cases., 2015)
Cummins Generator Technologies India Limited (CGTIL) was in the process of setting up a world-class factory at Ranjangaon based on "lean" production principles. The project team, however, went a step ahead and married "green" with "lean". While lean is about taking the system inefficiencies out, the green is about harmony with nature. The case is about CGTIL's journey of deriving synergies between seemingly conflicting objectives of lean and green.